Proliferation of Isoëtalean Lycophytes During the Permo-Triassic Biotic Crises: A Proxy for the State of the Terrestrial Biosphere - Looy, Cindy V.; van Konijnenburg-van Cittert, Johanna H. A.; Duijnstee, Ivo A. P. (Frontiers in Earth Science, 2021)
Throughout their 420-Ma-long history, Lycopodiopsida have played a subordinate role at the landscape level with very few exceptions. One being the arborescent Lepidodendrales that dominated Pennsylvanian peat swamps in equatorial regions. Another is the enigmatic world-wide proliferation of sub-arborescent Isoëtales during, and in the aftermath of the Permo-Triassic terrestrial biosphere crisis that extended deep into the Triassic. Palynological as well as megafossil data shows that in a great proportion of locations around the globe that produced a fossil record, the provincial floras characteristic for the latest Permian were replaced by communities dominated by Isoëtales such as Pleuromeia and its allies. Our analysis of the isoëtalean biology, especially of the genus Pleuromeia, reveals an unusual suite of physiological and life-history traits, all indicating that it was an excellent stress-tolerator, but also a slow-growing weak competitor. This enabled Pleuromeia to thrive during environmental crises and occupy diverse habitats following the decline of other plants groups. Given their unusual biology, Isoëtales’ repeated ubiquity throughout the Early Triassic implies prolonged and repeated environmental stress in localities worldwide. Additionally, it demonstrates that the cosmopolitan isoëtalean-dominated systems produced a low-productivity, low-diversity terrestrial trophic base of the food web that no longer provided the same level of ecological and evolutionary goods and services (energy source, niche construction, ecosystem engineering, etc.) as the communities they replaced.